Variant-Specific Surface Protein Switching in Giardia lamblia - Nash, T. E. (American Society for Microbiology, 2001)
Surface antigen switching in Giardia lamblia was analyzed using monoclonal antibodies specific for two variant-specific surface proteins (VSPs). Two VSPs were detected on the surface of single trophozoites. Dual expression persisted for 13 h but disappeared at 36 h, as in other parasites that undergo surface antigenic variation.